2014
DOI: 10.7166/25-3-502
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Co-Curricular Interventions to Strengthen Female Engineering Students’ Sense of Self-Efficacy and to Improve the Retention of Women in Traditionally Male-Dominated Disciplines and Careers

Abstract: Self-efficacy relates to positive outcomes for women studying and working in traditionally male-dominated fields such as engineering, science, and technology. Many women engineering students (WES) experience fear and insecurity about how they will be treated and perceived in this traditionally male-dominated field, either as a WES or as a working engineer. This study provides support for the development of co-curricular interventions to improve the self-efficacy of WES at a South African tertiary institution. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 23 publications
1
10
0
1
Order By: Relevance
“…There seemed to be a strong relationship between the degree of bias and the level of resistance on the part of the girls; in the cases where gender bias was explicitly reiterated, there was markedly higher degrees of resistance to such stereotype threats [27,42]. However, to address gender inequity in STEM, more work at the social level and at school level is required [6,29,34,44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There seemed to be a strong relationship between the degree of bias and the level of resistance on the part of the girls; in the cases where gender bias was explicitly reiterated, there was markedly higher degrees of resistance to such stereotype threats [27,42]. However, to address gender inequity in STEM, more work at the social level and at school level is required [6,29,34,44].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing self-efficacy can overcome the stigmatized stereotypes of women being perceived as not compatible for STEM fields [5,24]. Integrating STEM project-based learning into the curriculum and providing female role models can enhance STEM self-efficacy and professional commitment to engineering [33,34].…”
Section: Pathways To Improve Gender Equitymentioning
confidence: 99%
“…Participation in extra-curricular activities is one such strategy, as it allows students to demonstrate competencies not otherwise visible in their resumes due to limited job experience. Literature has revealed that participation in co-curricular activities bene ts students' retention rates and educational outcomes (Leung et al, 2011;Lourens, 2014).…”
Section: Rationale Of Studymentioning
confidence: 99%
“…This could give students and added psychological benefit that boosts confidence. If confidence, and therefore self-efficacy are increased, there is a clear added benefit to these students which research supports (11,12) . Based on discussions the authors had with several minority students, it is also possible that the peer role of the supplemental instructor plays is meaningful.…”
Section: Closing the Gapmentioning
confidence: 77%
“…The same confidence issues that ethnic minorities feel might explain this small decrease. The stigma that engineering is a male dominated career field can subconsciously affect female students by reducing their confidence and self-efficacy, and a correlation clearly exists between self-efficacy and success in STEM fields (11,12) .…”
Section: The Female Minoritymentioning
confidence: 99%